A politização da justiça constitucional e o papel do Supremo Tribunal Federal frente aos direitos fundamentais - Moreira, Carla Angélica (2017)
This work intends to analyze the Judiciary, in it's expanded political dimension, while investigation of judicial decisions, mainly by the Federal Supreme Court, which is challenged to act in the implementation of the well - known social question. Decisions related primarily to fundamental rights deserve greater concern, as to whether they invade competencies, legislative or executive, or only complying with the provisions of the Federal Constitution of 1988. The centrality of the Court - the form of the Judiciary as a whole - in decision-making about and some of the major national issues has generated applause and criticism and requires careful consideration of whether or not this process is appropriate. The growing politicization of the Judiciary has been largely due to the gaps left by other powers, which, by no assuming their new demands, end up transferring to the Judiciary the solution of problematic issues. To discuss these matters, this dissertation analyzes both The fundamental rights and constitutional values in the first chapter. The second chapter deals with the condition of the rule of law, the theory of the division of powers and its changes. And considers the big picture represented by the fulfillment of the role of the institutions in relation to the attributions of protection of fundamental rights. Its focused, in the third chapter, centrality of the Court, and to some extent the judiciary as a whole, in the problem solving of the major national issues. The quotas for blacks in public educational institutions is the focus of the fourth chapter. In the fifth chapter, we are interested in conceptualizing and differentiating the Politicization of the Judiciary from the. Judicialization of Politics, among other concepts brought by the specialists. The final considerations try to answer the question: the STF, as the guardian of the 1988 Political Charter, is fulfilling its mandate, especially with regard to fundamental rights, or exceeds its decisions, threatening democracy and the division of Powers and, consequently, the Democratic State of Law, building a government of judges?